2014
DOI: 10.1590/1413-81232014191.1901
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação e nutrição na Estratégia Saúde da Família em cinco municípios brasileiros

Abstract: Alimentação e nutrição na Estratégia Saúde da Família em cinco municípios brasileiros Food and nutrition in the Family Health Strategy in five Brazilian citiesResumo Trata-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
29

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 7 publications
2
5
0
29
Order By: Relevance
“…Regarding the demographic profile, the predominance of female nutritionists and in the age groups between 20-39 years is comparable to that verified in other studies, which revealed the feminization of the profession and the performance of young adults [9,[16][17][18]. This profile may be related to the cultural connotation, in Brazil, of the role of women as caregivers [19] and the short time of existence of the profession [16].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Regarding the demographic profile, the predominance of female nutritionists and in the age groups between 20-39 years is comparable to that verified in other studies, which revealed the feminization of the profession and the performance of young adults [9,[16][17][18]. This profile may be related to the cultural connotation, in Brazil, of the role of women as caregivers [19] and the short time of existence of the profession [16].…”
Section: Discussionsupporting
confidence: 81%
“…The lack of working conditions in relation to infrastructure, anthropometric equipment, resources for the development of daily activities, including those related to food and nutrition, found in a recent study with nurses, physicians and nutritionists of FHS teams [17], coincides with the main factors highlighted in this study. Difficulties related to the infrastructure of health facilities, including anthropometric equipment, were also highlighted in a literature review on growth surveillance in the country's Primary Health Care network [25].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Pimentel et al 18 reported that the Primary Health Care, through the FHS, is the appropriate environment for promoting food and nutrition activities with great impact on families. Taking as an example, the control of primary malnutrition and the lack of micronutrients, such as anemia and hypovitaminosis A.…”
Section: Resultsmentioning
confidence: 99%
“…Desse modo, as equipes de ESF são consideradas elementos fundamentais para apoiar a realização da Vigilância Alimentar e Nutricional (3) . Contudo, estudos mostram que diversos problemas na atenção básica dificultam a implementação do SISVAN nos municípios brasileiros, como a falta de equipamentos antropométricos, a sobrecarga de trabalho dos profissionais, internet lenta, falta de profissionais para a digitação dos dados, alta rotatividade de profissionais e a insuficiência de nutricionistas na operacionalização das atividades (4,5) .…”
Section: Introductionunclassified